2002
DOI: 10.1136/adc.87.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene levels in a contemporary population cohort are associated with wheezing and atopic eczema in preschool infants

Abstract: Background: The hygiene hypothesis states that insufficient exposure to certain infectious agents during childhood increases the risk of developing asthma and atopic diseases. Improvements in hygiene levels may be partly responsible for this decline in exposure. Aims: To assess whether hygiene levels in infancy are associated with wheeze and/or atopic eczema, independent of a number of possible confounding factors. Methods: Data were gathered from the Avon Longitudinal Study of Parents and Children (ALSPAC). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 15 publications
1
63
0
1
Order By: Relevance
“…The long-term effects of an inflammatory challenge at or near parturition in the human appear to be overwhelmingly negative (1,16,64,74). However, it is also known that lack of exposure to appropriate immune stimuli in childhood can enhance the risk of developing autoimmune diseases (62,73). We have seen in the rodent that a P14 challenge with LPS does not lead to obvious deficits in the later life ability to respond to a dose of LPS sufficicent to produce sepsis (79).…”
Section: Discussionmentioning
confidence: 70%
“…The long-term effects of an inflammatory challenge at or near parturition in the human appear to be overwhelmingly negative (1,16,64,74). However, it is also known that lack of exposure to appropriate immune stimuli in childhood can enhance the risk of developing autoimmune diseases (62,73). We have seen in the rodent that a P14 challenge with LPS does not lead to obvious deficits in the later life ability to respond to a dose of LPS sufficicent to produce sepsis (79).…”
Section: Discussionmentioning
confidence: 70%
“…36,37 The increasing use of soaps, shower gels, shampoos, and other harsh cleansing products, 38 especially in developing country cities undergoing rapid economic change, could be one reason for the comprehensive increase in eczema prevalence observed in our study and is further supported by a previous cohort study that showed an independent association between an increased hygiene score (that included the frequency of washing/wiping hands and faces and bathing practices of young children) and subsequent eczema risk. 39 …”
Section: Main Findingsmentioning
confidence: 97%
“…From these responses, the child's mean hygiene score was derived (ranging from least hygienic to most hygienic). 15 Similarly, a mean infection score was created from questionnaires for the age periods Ͻ6 months, 6 to 18 months, 18 to 30 months, 30 to 42 months, and 59 to 81 months, which gave values from 0 to 7. The infection score at each time point was the number of infections (diarrhea, vomiting, cough, high temperature, cold, earache, and ear discharge) reported.…”
Section: Measures Of Previous Infection and Hygiene Practicementioning
confidence: 99%